Evaluation of Long-Term Phosphorus Fertilizer Placement Effect on Soil Phosphorus and Crop Yield - M. J. Coelho; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2021)
Phosphorus (P) accumulation in soil with long-term P fertilizer placements can result in a potentially large available reserve of this nutrient for subsequent crop production. This study investigated the effect of phosphorus fertilizer management (placement: broadcast versus deep band) after ten years on soil P, and yield response of crop rotation. Field studies were conducted for a period of ten years in Manhattan, KS. Three treatments were evaluated: 1) control with no P fertilizer application and two fertilizer treatments (80 lb P2O5/a); 2) surface broadcast; and 3) deep band at approximately 4- to 6-in. depth. All treatments received strip-tillage. After ten years, soil samples were collected from the row at two sampling depths (0–3 and 3–6 in.), and the soil P and grain yield of 2015 were evaluated. The accumulation of large amounts of soil P was directly affected by P fertilizer placement. The broadcast P fertilizer placement increased the soil P by the resin method in the topsoil (0–3 in.) and deep band in the subsoil (3–6 in.). Broadcast and deep band placements had the same effect on grain yield of corn and soybean, however, the deep band showed an average lower grain yield for wheat than broadcast.
Keywords: Phosphorus; fertilizer placement; long-term